Ebeneser House, Main Model - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2022)
Ebeneser House is a kindergarten that was built in 1908 in Helsinki. It was one of the first kindergarten that was free for the working class in the Nordic countries and the pedagogics of Fröbel was practiced by is users. The education was practical and the children participated in both cooking and garden activities. A loving relation between the student and the teachers was important. The style of the building is Art Nouveau and it is still used as a kindergarten as well as a museum.
Ebeneser House, Main Model